The Antichità Romane of Piranesi: a project for cataloguing and conservation of the ancient ruins during the 18th Century - Rodrigues, Angela Rosch (Revista CPC, 2019)
During the 18th century, the interest for the architecture of the Classical Antiquity was amplified through archaeological discoveries in the Italic Peninsula. In this context, the architect, archaeologist and engraver Giovanni Battista Piranesi played a prominent role in the development of issues related to the historicization of architecture. From his fascination for the ruins and the observation and gauging of the remains in loco, especially from Rome and the surroundings, Piranesi established himself as an intellectual and artistic reference using engravings and texts as his main rhetorical instruments. This work aims to verify the influence of Piranesi for the observation and preservation of the past by cutting off one of his masterpieces: Antichità Romane (1756) – a four volume publication based on the preservation of antiquities by cataloguing. The documentary and creative approach adopted for the Antichità Romane had great repercussions nourishing the debates on the research of the current past and presented reflections that guided the precepts of the modern restoration which would be crystallized from the beginning of the 19th century. It can be concluded that Piranesi made a relevant contribution to the maturation of the way of relating to the past, with studies and preservation of the ruins through principles that would become fundamental for restoration, such as: detailed survey, analysis of buildings through hypothetical reconstitutions, and the predisposition to the declared interest in conservation and minimal intervention.